2016
DOI: 10.1002/pi.5108
|View full text |Cite
|
Sign up to set email alerts
|

Novel poly(3‐hydroxybutyrate) composite films containing bioactive glass nanoparticles for wound healing applications

Abstract: Bioactive glass (BG) is considered an ideal material for haemostasis as it releases Ca 2+ ions upon hydration, which is required to support thrombosis. In this study the effect of the presence of the BG nanoparticles in P(3HB) microsphere films on the structural properties, thermal properties and biocompatibility of the films were studied. The nanoscaled bioactive glass with a high surface area was also tested for its in vitro haemostatic efficacy and was found to be able to successfully reduce the clot detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…This is higher than that reported in the literature for PHAs. The average protein adsorption for PHAs was within the range 0.12-0.35mg/cm 2 [45][46][47]. In another study , Rai et al, 2010 reported the amount of serum proteins adsorbed on the P(3HO) films to be 0.083 mg/cm 2 [8].…”
Section: Characterization Of P(3ho-3hd-3hdd) Solvent Cast Filmsmentioning
confidence: 92%
“…This is higher than that reported in the literature for PHAs. The average protein adsorption for PHAs was within the range 0.12-0.35mg/cm 2 [45][46][47]. In another study , Rai et al, 2010 reported the amount of serum proteins adsorbed on the P(3HO) films to be 0.083 mg/cm 2 [8].…”
Section: Characterization Of P(3ho-3hd-3hdd) Solvent Cast Filmsmentioning
confidence: 92%
“…Recently a new class of dressings based on polymeric composite films, containing bioactive glass nanoparticles, appeared. These materials have been shown to induce haemostatic effect and optimization of tissue regeneration …”
Section: Introductionmentioning
confidence: 99%
“…The authors assumed that increased surface porosity and roughness, important parameters for osteoblast attachment on biomaterials, and decreased crystallinity caused by incorporation of gelatin is favorable for cell growth if compared with neat PHBHHx, thus making it more suitable as material for medical implantation [ 51 ]. Other studies describe the utilization of composites of PHA and inorganic materials such as bioactive glass [ 68 , 69 ], ceramics, or hydroxyapatite for tissue engineering to improve mechanical properties, degradation rate, and to impart bioactivity; these inorganic phases can be applied either as filler material in the PHA matrix, or as coating materials (reviewed by [ 30 ]).…”
Section: Pha-based Implants Sutures and Scaffolds For Tissue Engimentioning
confidence: 99%
“…Studying the effect of the particle roughness caused by hydroxyapatite formation on cell adhesion, cell differentiation, and cell mobility was carried out by immersing the composite films in simulated body fluid up to one week; after some days, the surface became rough and uneven. When testing the biocompatibility of the composites with enhanced surface roughness, lower protein adsorption capacity and reduced cell adhesion were observed, indicating that surface roughness of such nanoparticles has a zenith that should not be surpassed in order to prevent deleterious effects on cell adhesion and differentiation [ 68 ]. Using a 3D-bioplotter, the team of Zhao et al produced 3D-scaffolds of composites of PHBHHx and mesoporous bioactive glass.…”
Section: Pha-based Implants Sutures and Scaffolds For Tissue Engimentioning
confidence: 99%